Halofuginone inhibits tumor migration and invasion by affecting cancer-associated fibroblasts in oral squamous cell carcinoma - Wang, Danni; Tian, Mei; Fu, Yong; Sun, Yawei; Ding, Liang; Zhang, Xiaoxin; Jing, Yue; Sun, Guowen; Ni, Yanhong; Song, Yuxian (Frontiers in Pharmacology, 2022)
Oral squamous cell carcinoma (OSCC) is the most common malignant tumor in the oral and maxillofacial regions, with a high rate of metastasis. Cancer-associated fibroblasts (CAFs) play critical roles in tumor growth, metastasis and invasion, making them attractive therapeutic targets for cancer treatment. As an old anti-coccidiosis drug for poultry, Halofuginone (HF) has also been reported to possess anti-fibrosis and anti-cancer activities in the recent decades. However, whether it works by targeting CAFs in OSCC, and the mechanisms involved remain unclear. In the present study, we observed HF dose-dependently inhibits OSCC-derived CAF viability and proliferation. Meanwhile, HF decreased the expressions of α-SMA, FSP-1 and PDGFRβ, markers of the malignant phenotype of CAFs, both at mRNA and protein levels. Furthermore, functional studies demonstrated that HF dramatically attenuates the promotion effect of CAFs on OSCC cell migration and invasion. Mechanistically, the inhibition of MMP2 secretion and the upstream TGF-β/Smad2/3 signaling pathway played an important role in these processes. In the orthotopic transplanted tongue carcinoma in mice model, we confirmed that HF administration inhibited tumor growth and lymph node metastasis (LNM) with reduced CAF population, MMP2 expression and collagen deposition in tumor. Altogether, these results indicate that HF can inhibit the migration and invasion of OSCC by targeting CAFs, which will provide new ideas for the treatment of OSCC.